Localization of C-protein isoforms in chicken skeletal muscle: ultrastructural detection using monoclonal antibodies (The Rockefeller University Press, 1984)
Monoclonal antibodies (McAbs) specific for the fast (MF-1) and slow (ALD-66) isoforms of C-protein from chicken skeletal muscle have been produced and characterized. Using these antibodies it was possible to demonstrate that skeletal muscles of varying fiber type express different isoforms of this protein and that in the posterior latissimus dorsi muscle both isoforms are co-expressed in the same myofiber (17, 18). Since we had shown that both isoforms were present in all sarcomeres, it was feasible to test whether the two isoforms co- distributed in the same 43-nm repeat within the A-band, thereby establishing a minimum number of C-proteins per repeat in the thick filaments. Here we describe the ultrastructural localization of C- protein in myofibers from three muscle types of the chicken using these same McAbs. We observed that although C-protein was present in a 43-nm repeat along the filaments in all three muscles, there were marked differences in the absolute number and position occupied by the different isoforms. Since McAbs MF-1 and ALD-66 decorated the same 43- nm repeats in the A-bands of the posterior latissimus dorsal muscle, we suggest that at least two C-proteins can co-localize at binding sites 43 nm apart along thick filaments of this muscle.